Increased soluble IL-7 receptor concentrations associate with improved IL-7 therapy outcomes in SIV-infected ART-treated Rhesus macaques - Steele, Amanda K.; Carrasco-Medina, Lorna; Sodora, Donald L.; Crawley, Angela M. (Université d'Ottawa | University of Ottawa, 2017)
The use of interleukin-7 (IL-7) as an immunorestorative therapeutic has proven effective in HIV infection, cancer and bone marrow transplantation. Mediating its activity through membrane-bound IL-7 receptor α (mCD127), IL-7 therapy increases T-cell numbers and survival. A soluble form, sCD127, is found in plasma, and we have previously identified increased plasma sCD127 concentrations in HIV infection. Furthermore, patients with high sCD127 exhibited the best viral control, implicating a role for IL-7 or sCD127 directly in improved virologic/immunologic outcomes. The role of the cytokine IL-7 in elevating sCD127 levels was addressed here through assessment of retrospective samples obtained from SIV-infected antiretroviral (ART)-treated Rhesus macaques. IL-7 was administered in clustered weekly doses, allowing for an assessment prior, during and following IL-7 administration. The levels of sCD127 remained relatively unchanged during both early SIV infection and following initiation of ART. However, treatment with IL-7 increased sCD127 concentrations in most animals, transiently or persistently, paralleling increased T-cell numbers, correlating significantly with CD8+ T-cell levels. In addition, proliferating CD4+ or CD8+ T-cells (measured by Ki67) increased in association with elevated sCD127 concentrations. Finally, a high concentration of sCD127 in IL7-treated animals was associated with increased retention of T-cells (measured by BrDU). In addition, a lack, or loss of viral control was associated with more pronounced and frequent elevations in plasma sCD127 concentrations with IL-7 therapy. In summary, plasma sCD127 levels in SIV-infected ART-treated macaques was associated with therapeutic IL-7 administration, with higher sCD127 levels in macaques demonstrating the best T-cell responses. This study furthers our knowledge regarding the interrelationship between increased IL-7 levels and elevated sCD127 levels that may have implications for future IL-7 immunotherapeutic approaches in HIV-infected patients.
Keywords: Animals; Anti-Retroviral Agents; CD8-Positive T-Lymphocytes; Cell Survival; Interleukin-7; Lymphocyte Activation; Lymphocyte Count; Macaca mulatta; Receptors, Interleukin-7; Simian Acquired Immunodeficiency Syndrome; Simian Immunodeficiency Virus; Solubility; Treatment Outcome